STUDI LITERATUR REVIEW: PENGARUH SARANA PENYEDIAAN AIR BERSIH TERHADAP KEJADIAN DIARE PADA BALITA - Adilla Hafizah (CV. ADIBA ADISHA AMIRA, 2024)
Diarrhea is an environmentally based disease with high morbidity and mortality rates. The lack of provision of environmental sanitation facilities is a factor causing the high number of diarrhea cases. Most sufferers are children under 5 years of age or toddlers. The aim of this research is to determine the effect of clean water supply facilities on the incidence of diarrhea in toddlers. The selected journal benchmarks are journals published between 2019-2024 consisting of national journals and several official websites. Research using this method is carried out by comparing research methods, processing methods and the results obtained from each article. Based on the results and discussion, it was found that there is a significant influence between the provision of clean water on the incidence of diarrhea in toddlers. Water can be a source of disease because disease vectors, especially diarrheal diseases, multiply and spread through contaminated water. The availability of clean water is a factor that influences the incidence of diarrhea in toddlers. The conclusion obtained is that there is a proven relationship between the means of providing clean water and the incidence of diarrhea in toddlers. Therefore, it is recommended that the government and related agencies create good health programs to prevent and reduce these diseases, such as providing clean water facilities in every resident's house.